2016
DOI: 10.1159/000450581
|View full text |Cite
|
Sign up to set email alerts
|

Activated Phosphorylated STAT1 Levels as a Biologically Relevant Immune Signal in Schizophrenia

Abstract: Objective: Activation of STAT1 is directly downstream of the cytokine receptors that signal from specific proinflammatory cytokines known to be dysregulated in schizophrenia (SZ), such as IFNγ, IL6, IL2 and IL10, as well as hypoxia, viral/bacterial infections and peptide growth factors. If the increased cytokine protein levels repeatedly observed in SZ have biological consequences, then the measurement of pSTAT1 is a logical step forward. Methods: Peripheral blood mononuclear cells (PBMCs) from controls (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Whether HERV-W expression may be a cause and/or consequence of inflammation is still the subject of debate. At least in vitro , our THP-1 cell culture results support the hypothesis that these transcripts can be secondary to inflammation, as the expression of HERV-W env and gag transcripts increased following treatment with two independent pro-inflammatory stimuli, IFN-γ and LPS, which activate the JAK-STAT1 and NF-κB signaling pathways shown to be dysregulated in individuals with schizophrenia (Sharma et al, 2016; Song et al, 2009). Interestingly, direct binding of transcription factors to HERV promoter elements following cytokine stimulation, and a subsequent increase in expression, has recently been demonstrated for the HERV-K family of endogenous retroviruses (Manghera et al, 2016).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Whether HERV-W expression may be a cause and/or consequence of inflammation is still the subject of debate. At least in vitro , our THP-1 cell culture results support the hypothesis that these transcripts can be secondary to inflammation, as the expression of HERV-W env and gag transcripts increased following treatment with two independent pro-inflammatory stimuli, IFN-γ and LPS, which activate the JAK-STAT1 and NF-κB signaling pathways shown to be dysregulated in individuals with schizophrenia (Sharma et al, 2016; Song et al, 2009). Interestingly, direct binding of transcription factors to HERV promoter elements following cytokine stimulation, and a subsequent increase in expression, has recently been demonstrated for the HERV-K family of endogenous retroviruses (Manghera et al, 2016).…”
Section: Discussionsupporting
confidence: 76%
“…Persistent sub-clinical inflammation, primarily characterized by elevated expression of proinflammatory cytokines, including IL-6, TNF-α and IFN- γ, is a well replicated finding in the schizophrenia literature (Chase et al, 2016, 2015; Miller et al, 2011). Additionally, we and others have shown that corresponding inflammatory cell signaling pathways (JAK-STAT1 and NF-κB) are also affected (Sharma et al, 2016; Song et al, 2009). However, the explanation for and potential pathophysiological consequences of inflammation in this disorder remain to be established.…”
Section: Introductionmentioning
confidence: 71%
“…Altered immune system activity has been repeatedly demonstrated in individuals with schizophrenia and bipolar disorder, though a clear mechanistic understanding of the cause and consequence of immune activation remains to be elucidated (Beumer et al, 2012; Miller and Goldsmith, 2016). We have recently shown that a subset of individuals with schizophrenia have elevated levels of phosphorylated STAT1 (pSTAT1-Y701) in peripheral blood mononuclear cell (PBMC) nuclear extracts, indicating activation of the JAK/STAT1 signaling pathway (Sharma et al, 2016). This pathway is involved in the activation of myeloid cells to an inflammatory phenotype and is downstream of a number of keymembrane cytokine receptors, including interferon gamma (IFN-γ), which demonstrates altered expression in schizophrenia (Miller et al, 2011; Rauch et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both the JAK-STAT1 and NF-κB pathways, which demonstrate elevated activity in schizophrenia, require defined activity by catalytic enzymes such as kinases [4, 7, 8]. JAK inhibitors, such as tofacitinib and ruxolitinib have shown efficacy in clinical trials for a number of immune disorders, and tofacitinib has been approved for use in rheumatoid arthritis [94].…”
Section: Treatmentsmentioning
confidence: 99%
“…Gene expression profiling of circulating peripheral blood mononuclear cells (PBMCs) also demonstrates increased mRNA expression of these cytokines [46]. Additionally, there is evidence that cell signaling pathways critical in inflammation, NF-κB and JAK-STAT1, are activated to a greater degree in PBMCs from some individuals with schizophrenia compared to controls [4, 7, 8]. Excess inflammation can be accompanied by oxidative and nitrosative stress, and there is evidence in schizophrenia of increased markers such as iNOS, COX-2 and PGE 2 , as well as decreased antioxidant status [911].…”
Section: Introductionmentioning
confidence: 99%